Fatty acid composition of milk produced in organic and conventional dairy herds in Italy and Slovenia - J. Salobir (Italian Journal of Animal Science, 2010)
Thirty eight bulk milk samples were collected from 19 organic and conventional farms in Italian Region of Friuli Venezia Giulia and Slovene Regions of Obalno-Krasˇka and Gorisˇka with the aim to determine variation in fatty acid (FA) composition between two States and between two production systems. Results show that milk from Slovene organic farms contain the highest proportion of saturated FA (SFA; 70.32 %) and the lowest proportion of monounsaturated FA (MUFA; 25.49 %). Milk from both production systems in Slovenia contained greater proportions of n-3 polyunsaturated FA (PUFA; 0.99 and 1.20 % in conventional and organic farms, respectively) and lower proportions of n-6 PUFA (2.60 and 2.33 % in conventional and organic farms, respectively) than Italian milk samples (0.54 and 0.68 % n-3 PUFA and 3.03 and 3.39 % n-6 PUFA in conventional and organic farms, respectively). The ratio between n-6 and n-3 PUFA was thus lower in Slovene than in Italian milk samples, yet they did not differ statistically between production systems within the States. Slovene milk samples contained higher proportions of conjugated linoleic acid (CLA; 0.72 and 0.64 % in conventional and organic farms, respectively) than Italian milk samples (0.45 and 0.49 % in conventional and organic farms, respectively).